The Influence of Celebrity Endorsement Brand Image and Testimony on Purchase Interest in Scarlett Whitening Products in Pekanbaru - Achmad Tavip Junaedi; Nicholas Stanley; Amries Rusli Tanjung; Sri Indrastuti; Deby Tri Agustin; Nicholas Renaldo (Journal of Entrepreneurial and Business Diversity, 2026)
Purpose:The purpose of this research is to analyse the effect of celebrity endorsement on buying interest in Scarlett Whitening products to analyse the effect of brand image on buying interest in Scarlett Whitening products. Whitening To analyse the effect of Brand Image on buying interest in Scarlett Whitening products to analyse the effect of testimonials on buying interest in Scarlett Whitening products.Methodology:The research method uses quantitative methods, The sample in this study were 120 respondents. The sampling method in this study uses a type of non-probability sampling. The analysis method used multiple linear regression using the SPSS software test tool.Findings:The results showed that there is an effect of celebrity endorsement on product purchase intention. There is an influence of brand image on product purchase intention. There is an influence of testimonials on buying interest productImplication:It is suggested to the company, that the results of this research are expected to be used as a reference to correct, research and make improvements as necessary in the next research.